Papillary Serous Carcinoma of the Uterine Cervix with Lung Metastasis - Maliha Khan; Alan D. Gilman; Sobia Nizami; Aram Barbaryan; Alaa M. Ali; Aibek E. Mirrakhimov (Case Reports in Oncological Medicine)
Papillary serous carcinoma of the uterine cervix is a rare histological variant of cervical adenocarcinoma, with a very small number of cases reported. It is an aggressive tumor and is usually diagnosed at advanced stages by the time of diagnosis. Early-stage tumors can be treated with surgery and/or radiotherapy, while late-stage tumors have been treated with chemotherapy plus radical surgery with intermittent success. Here we report a case of metastatic papillary serous carcinoma observed at our hospital, which has been treated with debulking surgery and combination chemotherapy with carboplatin and paclitaxel.